The relationship between teacher multiple intelligences and self efficacy in adult TEFL : a case of a Language Academy / Mohammadreza Soofinajafi - Soofinajafi, Mohammadreza (2012)
It is assumed that self-efficacy unlike self-esteem or self-concept is a task-based phenomenon and its beliefs are strong controller of one's behavior; Pajares (2006). In this study a correlation is identified between teacher self-efficacy and Gardner's seven original intelligences. Two momentously important gaps are addressed as the research problems; firstly, teachers should be able to actualize and perform MI activities in the course books using their own respective intelligences. Secondly, it determines which intelligence(s) have a strong impact on self-efficacy. Mix mode methodology is employed meanwhile it uses a SPSS package with a sample size of 217 for a population of 500 teachers. The questions call for associative or correlational research as the quantitative part accompanied with an interview for its qualitative component. Different kinds of analysis such as T-test, ANOVA, and Multiple Regressions are done to determine the results at their maximum accuracy. The results represent that all the seven intelligences have a positive correlation with the level of efficacy. The implications have many practical applications in the future of the teacher training. By the same token, the results provide us with a new outlook on teacher assessment and employment. By and large, the efficacy and all the intelligences were positively and significantly correlated. The correlation appears to be more significant in personal intelligences that is to say interpersonal intelligence ranked first and intrapersonal intelligence second. In brief, the investigated order of the strength level of these positive co-relations is: 1) Interpersonal 2) Intrapersonal 3) Mathematical 4) Musical 5) Linguistic 6) Bodily-Kinesthetic 7) Visual.